2006
DOI: 10.1109/jproc.2006.876966
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Multiagent Teams and Sliding Autonomy for Large-Scale Assembly

Abstract: Recent research in human-robot interaction has investigated the idea of Sliding, or Adjustable, Autonomy, a mode of operation bridging the gap between complete robot autonomy and full teleoperation.This work, by and large, has been in single-agent domains -involving only one human and one robot -and has not examined the issues that arise when moving to multi-agent domains. Here, we discuss the issues involved when adapting Sliding Autonomy concepts to coordinated multi-agent teams. In our system, remote human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 17 publications
0
71
0
5
Order By: Relevance
“…Some of these target construction systems for specific tasks, such as structure assembly in extraterrestrial settings (Stroupe et al 2006;Huntsberger et al 2003), in orbit (Everist et al 2004;Ueno et al 2003), or for assembling vertical trusses (Lindsey et al 2011). Some works explore how to integrate a human in the loop to handle contingencies (Sellner et al 2006). With the same engineering orientation, architects (Gramazio 2008) and the construction industry (Gambao et al 2000) have shown a long-lasting interest in automation and robotic approaches (Skibniewski and Wooldridge 1992;Zavadskas 2010).…”
Section: Related Workmentioning
confidence: 99%
“…Some of these target construction systems for specific tasks, such as structure assembly in extraterrestrial settings (Stroupe et al 2006;Huntsberger et al 2003), in orbit (Everist et al 2004;Ueno et al 2003), or for assembling vertical trusses (Lindsey et al 2011). Some works explore how to integrate a human in the loop to handle contingencies (Sellner et al 2006). With the same engineering orientation, architects (Gramazio 2008) and the construction industry (Gambao et al 2000) have shown a long-lasting interest in automation and robotic approaches (Skibniewski and Wooldridge 1992;Zavadskas 2010).…”
Section: Related Workmentioning
confidence: 99%
“…The literature for traded control has typically focused on trading control between full autonomous control and full manual (user) control [12], [13]. In [12], the autonomous agent would take control when precise movements are needed during grasping with the user in full control otherwise.…”
Section: Related Workmentioning
confidence: 99%
“…In [12], the autonomous agent would take control when precise movements are needed during grasping with the user in full control otherwise. Examining whether the user or the autonomous agent should initiate traded control was examined in [13]. The user could take control if they determined that the robot was struggling with a task.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A good coordination system should avoid or minimize the occurrence of these problems by optimizing the use of resources and the time required to achieve the objectives [14]. Effective coordination between agents operating in a shared environment contributes to improving the quality of the solutions achieved and to improved performance in solving tasks [15].…”
Section: Introductionmentioning
confidence: 99%